2021
DOI: 10.1161/circoutcomes.121.008099
|View full text |Cite
|
Sign up to set email alerts
|

Grappling With Racial Health Inequity in Pediatric Cardiology

Abstract: Incessant racial health inequalities across nearly every major health index reveals less about what patients have failed to feel and more about what systems have failed to do. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Interestingly, implicit bias from health care providers has been identified as a potential contributing factor to these disparities. 18 , 19 A study demonstrated the significant impact implicit bias has on provider decision making and judgments for their patients. 20 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, implicit bias from health care providers has been identified as a potential contributing factor to these disparities. 18 , 19 A study demonstrated the significant impact implicit bias has on provider decision making and judgments for their patients. 20 …”
Section: Discussionmentioning
confidence: 99%
“… 80 Multiple studies have shown that racial concordance between the physician and patient leads to better health outcomes. 19 , 80 , 81 For example, Greenwood et al found that the infant mortality rate for Black infants under the care of a Black physician halved compared with Black infants under the care of a White physician. 19 , 81 The Heritable Disorders in Newborns and Children now require CCHD screening as part of the Uniform Screening Panel for newborns to include additional testing to detect and diagnose a wider range of illnesses.…”
Section: Theme Analysismentioning
confidence: 99%
See 2 more Smart Citations